ENDOVASCULAR EMBOLIZATION OF RUPTURED BRAIN ARTERIOVENOUS MALFORMATION (AVM) - Gilbert Tangkudung; David Susanto; Corry N Mahama (Neurologi Manado, 2019)
AVM of the brain are anomalies of the blood vessels that are derived from maldevelopment of the capillary network, allowing direct connections between cerebral arteries and veins. The most common presenting symptoms are cerebral hemorrhage and seizures. Current therapeutic modalities include microsurgical resection, radiosurgery, endovascular embolization, and conservative treatment. Appropriate treatment regimen according to patient characteristics and AVM morphology. Endovascular embolization can used as primary therapy, particularly for smaller, surgically difficult AVMs that contain few arterial feeders. Male, 61 years old, presented with severe headache and weakness of right limbs suddenly. Headache especially felt on the left side, with Visual Analog Scale (VAS) = 8-9, Glasgow Coma Scale (GCS) was E4M6V5, and patient underwent brain Magnetic Resonance Imaging (MRI) which revealed a hemorrhage in the left frontal lobe with flow void sign around the lesion. Patient underwent palliative targeted embolization procedure with Onyx-18 in left precentralis artery and left frontal medial artery. The results obtained changes in angioarchitecture of malformed lesion in nidus size were significant with slowing flow to drainage veins. This case was follow up after 7 months with Brain MRI which revealed no nidus and flow void sign, and from the checked cerebral angiography revealed a very small nidus with significant hemodynamic changes. Keywords: Endovascular, embolization, ruptured, AVM